Soft Element – Decision Reasoning Framework For Green Development Projects - Azizi, Nurul Zahirah Mokhtar (2018)
Soft element (SE) relates to administrative aspects that are responsible for effective project mobilization. Although SEs are comparatively smaller in monetary percentage than hard elements, their role is critical to the management and control of project implementation and ensures the effective delivery of construction on site. As the nature of SE is elusive, relating elements of this nature directly to project decision is difficult. This research aims to develop a framework providing holistic representation of SE and explain how they affect project decisions. In developing this framework, the Resource Mobilization Theory and Rational Choice Theory are used as the underlying theories.